Metaphorical landscapes and the theology of the Book of Job : an analysis of Job's spatial metaphors - Joode, Johan de, (Vetus Testamentum, Supplements, 2018)
Metaphorical Landscapes and the Theology of the Book of Job demonstrates how spatial metaphors play a crucial role in the theology of the book of Job. Themes as pivotal as trauma, ill-being, retribution, and divine character are conceptualized in terms of space; its imagery is thus dependent on spatial configurations, such as boundaries, distance, direction, containment, and contact. Not only are spatial metaphors ubiquitous in the book of Job-possibly the most frequent conceptual metaphors in the book-they are essential to its theological reasoning. Job's spatial metaphors form a metaphorical landscape in which God's character and his creation are challenged in unprecedented ways. In the theophany, God reacts to that landscape. This book introduces a pragmatic synthesis of both conceptual metaphor theory and spatial semantics and it demonstrates their exegetical and hermeneutic potential.